The structural diversity and properties of nine new viologen based zwitterionic metal–organic frameworks. Issue 12 (3rd March 2016) - Aulakh, Darpandeep; Nicoletta, Anthony P.; Varghese, Juby R.; Wriedt, Mario
Abstract : A viologen based ligand has been explored as a functional building block to synthesize a series of nine new zwitterionic metal–organic frameworks with this contribution reporting on their structural, thermal and photochromic properties. Abstract : The neutral flexible viologen based ligand 1, 1′-bis(4-carboxybenzyl)-4, 4′-bipyridinium dibromide (H2 L Br2 ) and its self-assembly with first-row transition metals in an aqueous media leads to the formation of nine new zwitterionic (ZW) MOF materials with the following compositions: {[CuBr(L )]·(OH)·7H2 O} n (1 ); {[M4 (L )6 (OH2 )12 ]·2Br·3(bdc)·33H2 O} n with M = Mn (2 ), Co (3 ) and Ni (4 ), {[M(bdc)(L )1.5 ]·9H2 O} n with M = Cd (5 ) and Zn (6 ); {[Cu2 (3-pzc)2 (L )(OH2 )]·5H2 O} n (7 ); {[ZnCl2 (L )0.5 ]·0.33H2 O} n (8 ) and [Pd(HL)(Br)2 (NO2 )2 (OH2 )2 ] (9 ) (bdc = 1, 4-benzenedicarboxylate, pzc = 3-pyrazole carboxylate). These compounds were characterized by single-crystal X-ray diffraction (SCXRD), powder X-ray diffraction (PXRD), infrared spectrometry (IR), elemental analyses, thermogravimetric analyses (TGA) and differential scanning calorimetry (DSC). Interestingly, when the samples are exposed to UV irradiation, photochromic behavior is observed for the ligand only, whereas the ZW MOFs are found to be photochemically inert. The fundamental structural origin for this photo reactivity is discussed in detail, as well as an in-depth CSD analysis of important intra- and intermolecular parameters ofL -based MOFs.